The brightest night / 5. - Sutherland, Tui, 1978- (Wings of fire, 2014)
Sunny, one of the dragonets of destiny, feels guilty for leaving Starflight with Morrowseer when she finds him hurt, and fights to rescue him, but is caught up in her own trouble when she does.